Presentation - Arias-Méndez, Esteban (2024)
IEEE Latin American Electron Devices Conference (LAEDC) 2023 welcome you to this fifth edition. LAEDC is the flagship conference for EDS in Region 9 and offers an enriching opportunity to learn about many of the fields related to Electron Devices and novel technologies. This special issue is focused on the short papers related to EDS topics presented at the conference. At LAEDC 2023 we celebrated different events and sessions. The EDS R9 Summer School about “Design, Characterization, and Fabrication of Sensors and Integrated Circuits” at INAOE in Puebla, México, with 18 International and national speakers and more than 80 international student participants from 9 countries. We also had a WIE/YP panel session, a MOS-AK workshop, an EDS Mini Colloquium, a Humanitarian Technology Panel Session, the EDS Region 9 Chapters Summit 2023 (SRC meeting), and a series of free workshops open to public in an event called “Ingeniería abierta para la ciudadanía” held at the Zocalo of Puebla. For this 2023 edition we had 81 submissions received, 47 accepted papers presented, 16 posters, 105 participants from 21 countries. We hope you enjoy the selected short-papers below.